(untitled) (Journal of Oriental Studies, 2026)
This article presents a comprehensive study of sight simultaneous interpretation based on the Chinese-Russian language pair a specific type of oral translation where a written text is interpreted aloud in real-time as it is being read. The relevance of this research is determined by the growing demand for rapid and accurate multilingual communication at international events, where interpreters often work from written materials. The aim of the study is to identify the cognitive features and typical difficulties of this interpretation mode and to offer effective methodological recommendations for improving its quality. The research methodology includes theoretical analysis, comparative approaches, empirical observation of professional interpreters, and the generalization of practical experience. The findings reveal that the presence of a written source does not simplify the interpreter’s task; on the contrary, it demands high levels of concentration, rapid information processing, instant interpretation, and flexible adaptation to the text’s stylistic and semantic characteristics. The Chinese-Russian combination presents additional challenges due to significant grammatical and lexical differences between the two languages. The article provides practical guidelines for training interpreters in this specific form of interpretation, including techniques for developing anticipation, short-term memory, segmentation skills, and speech tempo control. The results of the study are valuable for professional interpreters, educators in the field of interpretation, and organizers of multilingual events. Keywords: sight simultaneous interpreting, oral-visual translation, interpreter competence, cognitive skills, translation difficulties, cross-linguistic communication, interpreting strategies.